A Review of Key Activities in Hydro Meteorological Disaster Management - Chuan, Ngam Min; Thiruchelvam, Sivadass; Ghazali, Azrul; Mustapha, Kamal Nasharuddin; Muda, Rahsidi Sabri; Jin, Ng Yu; Norkhairi, Fatin Faiqa; Yahya, Nora (International Journal of Engineering and Technology, 2018)
One of the most highlighted issues in the developing world of the 21st century is the hydrometeorological disasters. Developed and developing nations are all affected by the more prominent climate change. There has been a rise in disaster occurrences over the past decade that this has caused more attention to be given to the topic of disaster management especially to floods. The scale of these disaster events has also intensified and have broken past records with more destructive disasters. This paper intends to review the activities related to hydrometeorological disaster. Key activities are broken down into three different phases, namely pre-disaster, during disaster and post-disaster. Understanding the activities involved is pertinent to not only the lead agencies and non-governmental organizations but plays a bigger role for the vulnerable communities. In the past, communities were the last group to be participative in disaster risk reduction efforts. Today, communities are being engaged from early stage to empower them to be resilient towards the possibility of facing future flood disaster. Evacuation planning and logistics arrangement are key activities prior to the occurrence of any disaster which will ease the implementation of search and rescue operations. However during disaster, it is important for the early warning system to be functioning to alert the affected communities. People also need to be aware of the outbreak of diseases during flood disaster. Finally, post-disaster efforts focuses more on the restoration of damaged infrastructure as well as the mental state of the affected victims. Understanding these key activities will increase the awareness of stakeholders in reducing loss of life and minimizing damages towards properties.